Criticism and Philosophical Analysis of Shahab National Project (Multiple Intelligence) for Primary School Students - Ali Farsi; Jahanbakhsh Rahmani; Zohreh Saadatmand (Iranian Evolutionary Educational Psychology Journal)
Objective: The aim of this study was to evaluate and scrutinize the ideology behind the Shahab national program (multiple intelligence) among primary school students. Methods: The methodology employed is pragmatic in its objectives and descriptive-analytical in its approach to data collection, utilizing surveys and post-event analyses. The target population for this study encompassed all primary school students in Isfahan province during the academic year of 2022. By employing cluster sampling and the Cochran formula, a sample size of 250 individuals was determined. The instrument utilized for data collection in this study was the Gardner multiple intelligences questionnaire comprising 80 items. Results: The findings indicated that according to the participants, the strengths and weaknesses of the national Shahab program have a significant impact and were deemed acceptable and conventional. As per the respondents of the Fundamental Transformation of Education document, the fostering of talents contributes to the unique abilities and individual variances among students. The participants also noted the significance of nurturing the exceptional abilities of elementary school students. Conclusions: The results typically offer school planners and counselors the essential understanding and perspective to recognize and support exceptional abilities